THE EFFECT OF DIGITAL STORYTELLING TO THE LISTENING COMPREHENSION IN NARRATIVE TEXT ON EIGHTH GRADE STUDENTS AT SMP NEGERI 9 PEMATANG SIANTAR - Pasaribu, Septiana Hirawati; Efipanias Manihuruk, Leonita Maria; P. Hutabarat, Novra Melisa (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
The objective of this research was to determine how Digital Storytelling affected the listening comprehension of students. A quasi-experimental design and quantitative methodology were employed in this study. The research comprised two classes selected through purposive sampling: class VIII-4 served as the experimental class with 30 students, while class VIII-6 served as the control class with an equal number of students. The teaching method in the experimental class involved Digital Storytelling, while the control class received instruction through conventional teaching methods. Data were collected through pre-tests and post-tests, each consisting of 20 multiple-choice questions. Analysis of the data revealed that the mean score for the pre-test in the experimental class was 65.33, increasing to 80.83 in the post-test. In comparison, the control class had a pre-test mean score of 58.5, which increased to 69.16 in the post-test. Applying the t-test formula, the researchers found that the calculated t-value (2.4) exceeded the critical t-value (1.67155) with degrees of freedom (df) equal to 58. In summary, the Alternative Hypothesis (Ha) was accepted, and the Null Hypothesis (H0) was rejected. Thus, the study concludes that the use of Digital Storytelling had a significant effect on the listening comprehension of narrative texts among eighth-grade students at SMP Negeri 9 Pematang Siantar. The findings suggest that Digital Storytelling can be effectively applied as a teaching medium to enhance students' listening comprehension skills.